Hydrolyzable and condensed tannins resistance in Clostridium perfringens. (August 2015) - Redondo, L.M.; Dominguez, J.E.; Rabinovitz, B.C.; Redondo, E.A.; Fernández Miyakawa, M.E.
Abstract: Tannins added in the diet are being used to improve nutrition and health in farm animals as an alternative to antibiotic growth promoters and to control enteric clostridial diseases. However, the capacity of Clostridium perfringens to develop resistance under the selective pressure of tannins is unknown. The purpose of this study was to determine if C. perfringens possess the ability to develop resistance against tannins in comparison with antimicrobial agents. Susceptibility for 7 AGPs (antimicrobial growth promoters), 9 therapeutic antimicrobials and 2 tannin based extracts was determined for 30 C. perfringens strains isolated from poultry and cattle. Two susceptible strains were selected and cultured in presence of sub-inhibitory concentrations of tannins and AGPs for resistant sub-populations selection. Tannin resistance of C. perfringens isolates from both animal species revealed no statistically significant differences in MICs (minimum inhibitory concentration). Poultry isolates showed higher MICs to several AGPs compared with cattle isolates. All isolates were susceptible to the therapeutic antimicrobials tested, but avian isolates showed a significantly lower susceptibility to these antimicrobials which was highly correlated with an increased resistance to bacitracin and others AGPs. In-vitro selection of resistant clones suggests that C. perfringens was unable to develop resistance against tannins at least compared to AGPs like bacitracin and avilamycin. Avian origin strains, which were previously exposed to antibiotics showed higher resistance, compared to cattle origin strains. These results suggest that the evolution of resistance against tannins in C. perfringens would be more difficult and slower than to the determined AGPs. Highlights: Clostridium perfringens poultry strains are less susceptible to AGPs than cattle strains. Chestnut and quebracho tannins show inhibitory activity against C . perfringens . Exposure to AGPs selects less susceptible sub-populations faster than tannins.